MACAM TEKNIK BUDIDAYA TERHADAP PERTUMBUHAN DAN HASIL TANAMAN PADI (Oryza sativa L.) - Elik Murni Ningtias Ningsih (Agroland: Jurnal Ilmu-ilmu Pertanian, 2014)
Rice plants ( Oryza sativa L. ) as a staple food to meet the needs of carbohydrates. Kinds of paddy rice cultivation techniques will affect the conditions of growing media and plant growth. Intensification of rice cultivation techniques with intensive maintenance and the provision of nutrient needs of plants wear inorganic fertilizers. Aerobic rice intensification technique controlled by the organic-based irrigation system returns organic matter through organic fertilizer given rice straw able to improve the biological properties of the soil and increase root growth. The study was conducted to test various techniques of rice cultivation and intensification of rice intensification controlled aerobic organic based on the growth and yield of rice plants. Research compiled by Complete randomized block design with a single factor treatment. Kinds of treatment consisted of B1 : intensification of rice cultivation techniques, B2 : Mechanical controlled aerobic cultivation of rice intensification of organic-based with 1 plant/planting hole and B3 : Mechanical controlled aerobic cultivation of rice intensification of organic-based with 2 plants/planting hole. Each treatment was repeated as many as 6replicates. Observation of the growth of plant height, number of leaves and number of tillers. The observation that crop yields per hectare. The results showed that rice cultivation technique had no effect on plant height and number of leaves of the rice plant. Rice cultivation techniques affect the number of tillers and paddy crops. B2 treatment resulted in the highest number of tillers at 7:33 fruit/plant and the highest crop yields 9:06 tons/plant. Key Words : Cultivation of IPAT - BO, Rice, techniques of rice cultivation.